AN ANALYSIS OF HYPERBOLE IN THE SOUR ALBUM OF OLIVIA RODRIGO - pande putu intan sruti prapila maha wirta putri; Mela Tustiawati Ida Ayu (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2022)
Abstract Figurative language has an important role in literary works. One of them is song lyric. Many songwriters write their songs using figures of speech for the deep message they want to convey to their target. Therefore, the aim of this study is to find out how many figures of speech hyperbole are contained in the lyrics of Olivia Rodrigo's song on the album